Об испытаниях отечественного гидроперфоратора - Глущенко, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The brief description is presented of the large test rig designed for study and construction parameters determination of hydraulic perforators. The first results of this testings is presented also. The basic units of the rig were developed by specialists of DONUGI then transferred to FED Enterprise Kharkov where its assembly and operation development was executed.